Morbidity and Mortality of Nosocomial Infection after Cardiovascular Surgery: A Report of 1606 Cases - Jiang, Wan-li; Hu, Xiao-ping; Hu, Zhi-peng; Tang, Zheng; Wu, Hong-bing; Chen, Liang-hao; Wang, Zhi-wei; Jiang, Ying-an (Current medical science, 2018)
Summary Nosocomial infection (NI) is one of the most significant complications arising after open heart surgery, and leads to increased mortality, hospitalization time and health resource allocation. This study investigated the morbidity, mortality, and independent risk factors associated with NI following open heart surgery. We retrospectively surveyed the records of 1606 consecutive cardiovascular surgical patients to identify those that developed NI. The NI selection criteria were based on the Centers for Disease Control and Prevention (CDC) guidelines. The term NI encompasses surgical site infection (SSI), central venous catheter-related infection (CVCRI), urinary tract infection (UTI), respiratory tract infection and pneumonia (RTIP), as well as other types of infections. Of 1606 cardiovascular surgery patients, 125 developed NI (7.8%, 125/1606). The rates of NI following surgery for congenital malformation, valve replacement, and coronary artery bypass graft were 2.6% (15/587), 5.5% (26/473) and 13.6% (32/236), respectively. The NI rate following surgical repair of aortic aneurysm or dissection was 16.8% (52/310). Increased risk of NI was detected for patients with a prior preoperative stay ≥3 days (OR=2.11, 95% CI=1.39–3.20), diabetes (OR=2.00, 95%=CI 1.26–3.20), length of surgery ≥6 h (OR=2.26, 95% CI=1.47–3.47), or postoperative cerebrovascular accident (OR=4.08, 95% CI=1.79–9.29). Greater attention should be paid toward compliance with ventilator and catheter regulations in order to decrease NI morbidity and mortality following cardiovascular procedures.